ublic Universities of northeastern Argentina: indicators and practices of Public Communication of Science and Technology (Papeles, 2024)
This paper aims to reflect on three public universities in Northeastern Argentina (NEA) concerning the place they occupy in the Argentine scientific system and for the community through different indicators and surveys on science, technology, and innovation (STI) in Argentina and Latin America. We are interested in reflecting on these data and analyzing them in relation to public science communication (PSC) practices. First, we share our theoretical and methodological perspective to think about PSC and the role of universities in this area. Secondly, we analyze different indicators and results on the current STI situation at a national and regional level. Then, we begin to map PSC practices in three universities in the NEA: Universidad Nacional del Nordeste, Universidad Nacional de Formosa, and Universidad Nacional de Misiones. Finally, we offer some final reflections
Keywords: public communication of science and technology; scientific communication; university